Quality Management of the Pancasila Student Profile Project for Character Development - Ani Haryani; H Hidayat (CV. Media Digital Publikasi Indonesia, 2025)
Character education is one of the main focuses of the Kurikulum Merdeka (Independent Curriculum), implemented through the Pancasila Student Profile Strengthening Project (P5). This study aims to describe and analyze the quality management of P5 in enhancing student character, particularly in the aspects of collaboration (gotong royong) and independence, at the kindergarten level. A qualitative case study approach was employed. Data were collected through classroom observations, interviews with teachers, principals, and parents, as well as project documentation. The findings indicate that careful planning, participatory implementation, and continuous evaluation are crucial factors for the successful execution of P5. Challenges encountered include limited facilities, variations in parents’ understanding, and restricted time allocation. These issues can be addressed through teacher–parent collaboration, integrating projects into other learning activities, and developing contextual learning media. In conclusion, the quality management of P5 has proven effective in shaping children’s character from an early age, fostering awareness, independence, and collaborative spirit, while also preparing students to meet the demands of 21st-century education.